An experimental investigation on multi-cylinder RCCI engine fueled with 2-butanol/diesel. (15th December 2017) - Pan, Suozhu; Li, Xin; Han, Weiqiang; Huang, Yaxing
Highlights: The combustion and emission of 2-butanol RCCI operation mode were investigated. The COVIMEP of 2-butanol RCCI combustion mode was below 2% under various engine loads. The particle size distribution of 2-butanol RCCI combustion mode was analyzed. NOx and PM (including mass and number) can be simultaneously reduced by 2-butanol RCCI combustion mode. At high load, the BTE increases up to approximately 7.08% in 2-butanol RCCI combustion mode. Abstract: The purpose of current work is to experimentally investigate the combustion and emission of 2-butanol/diesel RCCI mode on a light-duty diesel engine under various engine loads. The results revealed the 2-butanol/diesel RCCI combustion mode has an accepted COV (coefficient of variation) in IMEP (indicated mean effective pressure), which was below 2% under various engine loads. Compared with CCM (conventional combustion mode), the RCCI combustion led to the increase of peak combustion pressure, maximum RoHR (rate of heat release), premixed combustion proportion and RoPR (rate of pressure rise), but also caused the decrease of RoHR duration as well as combustion temperature. The BTE (brake thermal efficiency) clearly decreased under low engine loads, but increased by approximately 7.08% under high engine loads. In addition, concurrent decrease of NOx and PM as well as increase of HC and CO were observed. Furthermore, the particle size distribution shifted towards small-particle-diameter range, accompanied with more marked shift tendency with the increase of the premixed ratio of 2-butanol.